Estimation Chlorophyll-a Using Landsat-8 Imagery in Shallow Water: Effect of Atmospheric and Algorithm - Abdi Sukmono; Lilik Kristianingsih (The IJICS (International Journal of Informatics and Computer Science), 2021)
Chlorophyll-a estimation using remote sensing technology is being challenged to improve its accuracy. Various algorithms and correction methods need to be studied, including the influence of the atmosphere. It can influence the passage of the electromagnetic wave from the sun to the object and from the object to the sensor that makes the difference on the image reflectance. There are two kinds of reflectance; which are ToA (Top of Atmosphere) reflectance and BoA (Bottom of Atmosphere) reflectance. ToA reflectance is the reflectance captured by the sensor yet BoA reflectance is the reflectance of the object corrected by the atmosphere. ToA reflectance is produced by radiometric calibration while BoA reflectance is made of atmospheric correction process. This research studies aims to compare those to reflectance to investigate the impact of atmospheric correction usage on chlorophyll-a case study. The waters of Wedung district is chosen as the research field because it is the largest area in Demak regency. This study used DOS (Dark Object Substractions), FLAASH (Fast Line of sight Atmospheric Analysis of Spectral Hypercubes), and 6SV (Second Simullations of a Satellite Signal in the Solar Spectrum) correction method. To compare between ToA and BoA reflectance in the calculation of chlorophyll-a, the writer used the algorithms of Wouthuyzen, Wibowo, Pentury, Much Jisin and also Lestari Laksmi. The result shown is that the usage of BoA image reflectance (atmospherically corrected) had a better model result than ToA image reflectance. This is indicated from the consecutive determination coefficient values of ToA reflectance which are 0,2292; 0,4562; 0,2292; 0,2252. Meanwhile the consecutive coefficient values of BoA reflectance by DOS correction method are 0,5251; 0,5575; 0,5251; 0,6939; by FLAASH correction method are 0,6168, 0,5041, 0,6168, 0,614; by 6SV method are 0,6436; 0,4033; 0,6436; 0,6365. The result of hypothesis and validation test is that atmospheric correction significantly influences on the calculation of chlorophyll-a in Wedung district except using Wibowo algorithm.